UTILIZATION OF ACCOUNTING INFORMATION SYSTEMS WITHIN THE CONTEXT OF SHARIA BANKING - Ikhsan Abdullah; Muhammad Salman; Nurlaila (CV. Radja Publika, 2023)
The development of Sharia banking is currently getting better, motivating people to use the Entity's products. Both Murabahah, Zakat, Sharia Insurance, Musyarakah. Transactions in this entity must be supported by a good accounting information system which will influence the resulting financial reports. This research discusses the implementation of accounting information systems in Sharia Banking. The research method uses a systematic literature review. The data collection method is by searching for articles, letters in the form of research journals related to Accounting Information Systems in their application to sharia banking, then pouring them into a theoretical framework. The research results found that the accounting information system in sharia banking is designed to comply with sharia principles such as the prohibition of interest, prohibition of speculation and fairness in the risks faced both in terms of profits and losses experienced. Accounting information systems in sharia banking include muamalah, murabahah, mudarabah, musharakah transactions, and others. The accounting information system produces financial reports that comply with sharia financial reporting standards. In addition, the accounting information system supports the audit process and sharia supervision to ensure compliance with sharia principles. In general, it can be concluded that the accounting information system in sharia banking plays an important role in improving the performance of sharia banking which is related to the use of sharia information technology, fulfilling government and competitor regulations, as well as meeting human resource needs. The accounting information system makes it possible for sharia banking to make various financial and accounting processes easier. Implementing AIS will reduce dependence on manual processes, which tend to be slower and error-prone.